The Scholia on Cicero's Speeches Contexts and Perspectives - Pieper, Christoph; Pausch, Dennis (Brill, 2023)
The ancient commentaries and scholia to Cicero's speeches have hitherto received relatively little scholarly attention. This volume is dedicated to Asconius' first-century commentary and the corpora of the scholia stemming from the 4th-7th centuries (Bobbio, ps.-Asconius, and Gronovius). It shows the specific interpretative challenges of these corpora and offers interpretative case studies. Furthermore, it contextualizes the corpora within the learning and learned environment of their time, by contrasting them with rhetorical teaching (via the transmission of Cicero on papyri and his presence in the Rhetores Latini minores) and other ancient commentaries (on Homer and Demosthenes).